2020
DOI: 10.1097/md.0000000000022586
|View full text |Cite
|
Sign up to set email alerts
|

Cupping for neurodermatitis

Abstract: Background: Neurodermatitis is a common inflammatory and allergic disease, characterized by itching and lichenification plaque. Some studies have reported cupping therapy (CT) for the treatment of neurodermatitis. However, the effectiveness and safety are still uncertain. This study aims to evaluate the efficacy and safety of CT for the treatment of patients with neurodermatitis. Methods: We will retrieve the following electronic databases systematically: Pubmed, Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…This study also showed a significant correlation between the intensity of pruritus as measured by the VAS and 5D on the quality of life of neurodermatitis patients using the DLQI. The same conclusion was drawn from previous studies which stated that the condition of neurodermatitis patients significantly affects the quality of life (Georgieva & Vankova, 2016;Goyonlo et al, 2017;Peng et al, 2020).…”
Section: Quality Of Life In Neurodermatitis Patientssupporting
confidence: 84%
See 1 more Smart Citation
“…This study also showed a significant correlation between the intensity of pruritus as measured by the VAS and 5D on the quality of life of neurodermatitis patients using the DLQI. The same conclusion was drawn from previous studies which stated that the condition of neurodermatitis patients significantly affects the quality of life (Georgieva & Vankova, 2016;Goyonlo et al, 2017;Peng et al, 2020).…”
Section: Quality Of Life In Neurodermatitis Patientssupporting
confidence: 84%
“…Neurodermatitis is not a life-threatening disease, but can have an impact on quality of life and cause a psychosocial burden (Georgieva & Vankova, 2016;Peng et al, 2020). The symptoms of pruritus in neurodermatitis are triggered by emotional stress or other itchy stimuli.…”
Section: Introductionmentioning
confidence: 99%